Pool boiling heat transfer during quenching in carbon nanotube (CNT)-based aqueous nanofluids: Effects of length and diameter of the CNTs. (25th July 2017) - Fan, Li-Wu; Li, Jia-Qi; Wu, Yue-Zi; Zhang, Liang; Yu, Zi-Tao
Highlights: Quenching of water-based nanofluids with CNTs of various sizes was investigated. Consecutive runs were shown to have accumulative effect on the quenching behavior. Quenching acceleration and boiling enhancement vary among the various CNT samples. Discrepancy in performance was related to surface roughness and morphology changes. Longer and thicker CNTs were preferred for easy formation of micro-porous layers. Abstract: Quenching experiments were performed with hot stainless steel spheres in a pool of saturated water-based nanofluids with carbon nanotubes (CNTs) of various sizes. A test matrix was developed by choosing multi-walled CNTs having four combinations of nominal lengths and outer diameters, while the concentration was fixed at 0.5% by mass. It was shown that the quenching process is progressively accelerated upon consecutive runs due to the accumulative deposition of CNTs. The relative quenching acceleration and boiling heat transfer enhancement were found to be strongly related to the size discrepancy among the CNTs, as a result of the various surface morphologies and properties of the deposition layers. The CNTs with a length of 5 μm and a diameter of 60 nm were exhibited to lead to the most remarkable enhancement on the quenching and boiling behaviors, with the critical heat flux and Leidenfrost point being increased by about 60% and 100% respectively, due to the easy formation of micro-porous layers by this type of longer and thicker CNTs. It was identified that the significantly increased surface roughness with porous structure, instead of the nearly unvaried surface wettability, is responsible for the enhanced boiling heat transfer during quenching. The findings of this work suggested an active approach to optimization of quenching performance of CNT-based nanofluids.